Antimicrobial activity of propolis and its effect on the physicochemical and sensorial characteristics in sausages - GUTIÉRRREZ-CORTÉS, Carolina; SUÁREZ MAHECHA, Héctor (Vitae, 2014)
Background: In the food industry, the use of natural additives capable of replacing chemical additives is increasing due to the tendency to consume natural and healthy foods. In nature, different substances such as propolis can fulfill that role and it is obtained from hives of honey bees. Propolis contains bioactive compounds with antimicrobial and antioxidant capacity, and thus, they could be used as an alternative for nitrites in meat products. Objectives : To evaluate the in-vitro antimicrobial activity of the ethanol propolis extract (EEP) of on some pathogenic bacteria and their influence on the physicochemical and sensorial properties of sausages. Methods: The ethanol extraction was performed, and its antimicrobial activity in vitro on S. aureus, Salmonella, E. coli and Clostridium spp. was determined. Sausages were prepared according to the following treatments: (1) EEP 0.8mg/mL, (2) 0.2g/Kg sodium nitrite and sodium erythorbate, (3) Alcohol (96% v/v used as control) and the physicochemical analysis was performed to determine thiobarbituric acid (TBA), volatile nitrogen bases (TVB - N) and sensoral tests every week for four weeks. Analysis of variance and Tukey test were performed and the level of significance was p < 0.05. Results: No significant differences between EEP concentration, pH and TVB-N or sensorial properties (p > 0.05) were found. However, significant differences in TBA values were observed (p < 0.05). Conclusions: A 0.8% EEP shows antimicrobial activity against some pathogenic microorganisms evaluated. Further, the physicochemical and sensorial characteristics of the product do not differ from the sausages containing nitrites.